DAKWAH PENGENDALIAN EGO SUNAN KALIJAGA TINJAUAN PSIKOANALISIS SIGMUND FREUD - Hasri, Feri Dhani (Jurnal Al-Hikmah: Jurnal Dakwah, 2022)
Abstract: This paper aims to describe the form of the ego control method used by Sunan Kalijaga in spreading his da'wah to Indonesian people, especially on the island of Java. Sunan Kalijaga is a scholar who is widely known for spreading Islam on the island of Java through art, he is also one of the figures of the nine saints who are better known as Walisongo. The ego referred to in this study is one of the three sub-theories of Sigmund Freud's Psychoanalysis in the form of; Id, Ego and Superego. The method used in this research is qualitative analysis, where words, phrases, and sentences become research data. The techniques used in collecting data are reading, recording, and document analysis with the Sunan Kalijaga dakwah method approach. The results of this study indicate that the da'wah method used by Sunan Kalijaga including meditation and contemplation, Both of these, when viewed from the perspective of Sigmund Freud's psychoanalysis, found similarities with the method used by Sigmund Freud, namely the Psychoanalysis Approach or the method of analyzing the structure of the human subconscious, but there are some significant differences. Meditation and contemplation is effective in controlling the human ego, especially Muslims todayKeywords: Ego, Sunan Kalijaga, Psikoanalisis, Sigmund Freud